ANALISIS KETAHANAN KOTA TERHADAP BENCANA BANJIR DI DAERAH ALIRAN SUNGAI ACAI KOTA JAYAPURA - Ade Irma Surnyany; Harmonis Rante; Mujiati Mujiati (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2021)
According to information from BNPB for the district/city of Jayapura, in the last 10 years from 2009 to 2019 natural disasters floods rank first in the number of events that have been experienced. The research was conducted in the Kali Acai river, Abepura District, Jayapura City. The research time is estimated to be ±2 months with data taken in the form of primary data and secondary data. The results of channel evaluation carried out both secondary and primary channels when compared with the maximum flood (Q plan) that occurred in the Acai Sub-watershed with a 10 year return period, amounted to 154.197 m3/sec. Meanwhile, the results of the evaluation of the Acai River's capacity are still quite large without sedimentation and garbage. The vulnerability of the urban community due to the flood disaster that occurs is seen from the social aspect including age, gender, and community education in Abepura District. From the variables, namely the age level of 28.36% and 1.35%, it has a relatively small population of disaster-prone groups. The gender variable shows that the number of vulnerable are women in the amount of 45.47% of the total population of male and female productive age, while the variable for the level of vulnerable education is 54.43% who have primary school education. Efforts that can be made by the government and society in flood control efforts are through structural and non-structural methods.